(untitled) (Research, Society and Development, 2020)
The present work aims to understand which aspects can contribute to broaden or awaken the interest of high school students in Biotechnology and Science, based on formal and non-formal teaching strategies. The research methodology is of a qualitative nature, involving action research. In the first stage of the study, a questionnaire was applied to 300 students from the 1st, 2nd and 3rd grades of a state school in Mauá - São Paulo, and 30 students were chosen with availability to participate in the second stage of the study (action research). The hypothesis of the study is that the incorporation of practical activities to the Science curriculum, added the opportunity to include experiences in non-formal spaces, as well as the debate in the classroom, could contribute to bring high school students closer to a more realistic notion of Biotechnology and its importance to society. As result of the study 73% of students expressed greater interest in knowing more about the subject after the interventions, indicative of motivation and satisfaction with new forms of learning. As a conclusion, from the data collected and analyzed it was possible to notice the importance of the diversity of learning situations and didactic resources used. The application of practical activities, allowed students to develop the capacity of observation, inference, measurement, communication, classification and prediction, integrated to the formulation of hypotheses, data interpretation and conclusion to the scientific process, promoting reflections and deeper debates among high school students of a public school.